Pengaruh Edukasi Dengan Media Sosial (Whatsapp) Terhadap Pemahaman Tentang Human Trafficking Pada Siswa SMK INOTEK Tempuran, Karawang, Jawa Barat - Luigisha Augusti, (2020)
Human Trafficking is a crime of human exploitation, especially in children and women. According to the KPAI, data of August 2019 reached 154 cases of Criminal Trafficking (TPPO) which exploited children. Based on annual reports of trafficking, since 2016-2019, Indonesia on the second in the world. The most cases, with one contributing factor is lack of public knowledge related to Human Trafficking. The purpose of this study to identify effect of providing education with social media (Whatsapp) to understanding of Human Trafficking in SMK INOTEK Tempuran students. The population of this study is student of SMK with a sample of 64 students. Methods of this study is Quasi Experiment Pre & Post Test Without Control. The results of the study showed that increase of knowledge level of Human Trafficking in the good category (65.68) while level of category level of attitude also from (60.64). Based on the bivariate analysis showed the influence of education with Whatsapp as education tool to understanding of human trafficking, with a p value of 0,000, it mean that the education has effect of knowledge and attitude. The researcher suggests that education about Human Trafficking be done directly and continuously.